One-neutron transfer, complete fusion, and incomplete fusion from the Be 9 + Au 197 reaction - Gollan Scilipotti, Fernando Daniel (2021)
In this work, one-neutron transfer (pickup and stripping), complete and incomplete fusion cross sections for the Be9+Au197 system were measured over a wide range of energies around the Coulomb barrier by the offline γ-ray detection method. Coupled-channel calculations were used to determine the elastic, inelastic, and transfer cross sections. Coupled reaction channel calculations were performed to derive the one-neutron stripping and pickup cross sections. Three-body continuum discretized coupled-channel calculations were used to determine the effect of the breakup channel on the other reaction mechanisms. The reduced complete and total fusion were found to be hindered above and enhanced below the Coulomb barrier compared with the universal fusion function due to the breakup plus transfer effects.